Electrospun submicron NiO fibers combined with nanosized carbon black as reinforcement for multi-functional poly(lactic acid) composites. (February 2020) - Zhang, Lu; Liu, Wei; Wen, Xin; Chen, Jiayin; Zhao, Chenshou; Castillo-Rodríguez, Miguel; Yang, Lingwei; Zhang, Xiu-Qin; Wang, Rui; Wang, De-Yi
Abstract: From the point of designing fiber reinforced multi-functional polymer composites, porous submicron nickel oxide (NiO) fibers were fabricated via electrospinning and subsequent pyrolysis process. Combined with nanosized carbon black (CB), the influences of NiO fibers on the mechanical properties and flame retardancy of polylactide (PLA) composites were investigated. The results showed the electrospun NiO fibers imparted higher tensile strength and modulus to PLA composites. With the increase of NiO fiber content in PLA composites, the Young's modulus, storage modulus from dynamic mechanical analysis and elastic modulus derived from nanoindentation test showed similar increasing trends. In addition, compared with commercial NiO particles, NiO fibers exhibited a better flame retardant effect, which was attributed to the formation of continuous and intact char layer network. The proposed combination of electrospun NiO fibers and nanosized CB in PLA matrix is expected to inspire new strategies to prepare multi-functional fiber reinforced polymer matrix composites.